Identifikasi Penyakit dan Gangguan Kesehatan Karang di Perairan Pomalaa Sulawesi Tenggara - Riska, Riska; Pariakan, Arman; Lalang, Lalang; Ardiansyah, Indra (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2025)
Coral reef ecosystems have an important role in maintaining the balance of the marine environment, providing habitat for various ecosystems, and supporting the existence of coastal and marine resources. However, coral is also vulnerable to being threatened by various diseases and health disruption which can cause a decline in its quality and sustainability. This research aims to identify types of diseases and coral health disruption, forms of coral growth infected with diseases and disruption, and analyze the prevalence of coral diseases in Pomalaa waters. Sampling was carried out at 4 observation points. The research used a survey method and a belt transect method, measuring 5 m x 50 m to identify coral diseases and health problems. The research results found 6 types of coral disease, namely Black Band Disease (BBD), White Syndromes (WS), Yellow Band Disease (YBD), Pink Plotch (PP), Ulcerative White Spots (UWS), and Red Band Disease (RBS). Coral health disruption are generally caused by coral bleaching, Crown of Thorns Starfish, Growth Anomalies, Pigmentation Response, and Sediment Damage. The decline in the quality of the aquatic environment plays a major role in the emergence of various diseases and disruption of coral health, which have an impact on physiological disturbances for coral biota. Meanwhile, the coral growth forms (lifeforms) that are infected are Acropora Branching, Acropora encrusting, and Coral Massive. The highest prevalence rate of coral disease was at station 1, while the lowest was at station 4. The high prevalence rate of corals was the result of a combination of various natural and anthropogenic factors. The low level of coral prevalence at station 4 is possible because this side is a windward area that is exposed to currents at all times, thus helping corals to clean sediment attached to the surface which may carry bacteria that cause disease and coral health disruption. Global warming, pollution, destructive fishing practices, and invasive species are some of the main causes that increase corals' vulnerability to disease and health disorders.